IMPORTANCE OF TECHNOLOGIES IN REDUCING FOOD LOSS IN OPEN-FREE MARKETS. - Abreu, Fabricio; Barros , Luciano (Revista Interface Tecnológica, 2024)
This article investigates the importance of technology in reducing food waste in open-air markets. The implementation of technological solutions, such as mobile applications and sensors, can optimize distribution and improve supply chain management. The aim of the work is to analyze how these innovations can minimize waste and promote more efficient distribution. Through bibliographic research, this study seeks to demonstrate the effectiveness of these technologies in food preservation.